Definition of a bacterial virulence factor: sialylation of the group B streptococcal capsule. - Wessels, M R (1989)
Sialylation of bacterial capsules has been proposed as an important virulence factor for several species of encapsulated pathogens, including group B Streptococcus. We have constructed a transposon mutant strain of type III group B Streptococcus that expresses a capsular polysaccharide differing from the wild type only in that the mutant strain's capsule lacks sialic acid. The mutant polysaccharide is antigenically identical to the capsular polysaccharide of type 14 Streptococcus pneumoniae, as predicted by the structures of the type III group B Streptococcus and S. pneumoniae polysaccharides. Loss of capsular sialic acid was associated with loss of virulence in the mutant strain in a neonatal rat model of lethal group B Streptococcus infection. These studies demonstrate directly that capsular sialic acid is a critical virulence determinant for type III group B Streptococcus and support the general hypothesis that surface sialylation aids pathogenic microorganisms in evading host defenses.